A high hoop stiffness polypropylene composition for pipes and a process for the preparation thereof

CN122898090APending Publication Date: 2026-10-13ZHEJIANG QIANDA PIPE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611354994.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种管材用高环刚度聚丙烯组合物及其制备方法,解决现有高刚性聚丙烯管材在采用无机填料改性时,填料极易诱导脆性α晶型生长并导致低温抗冲性能恶化,且常规刚性偶联处理无法缓解冲击应力,进而引发管材在低温施工环境中易发生脆性断裂的问题

Benefits of technology

1、本发明通过聚乙二醇对微细滑石粉进行预处理。聚乙二醇的端羟基与滑石粉表面的极性位点形成氢键吸附,钝化了滑石粉诱导α晶型生成的异相成核活性。这一空间屏蔽机制排除了填料对结晶路径的干扰,使体系中的稀土类β晶型成核剂能够充分发挥作用,在基体中稳定诱导生成具有应力吸收能力的β晶型,从而解决了传统高填料管材低温抗冲性能差的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898090A_ABST
    Figure CN122898090A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of chemical engineering and polymer materials, and discloses a kind of high ring rigidity polypropylene composition for pipe material and preparation method thereof, and the raw material of the composition includes by mass fraction: block copolymerization polypropylene, micro talcum powder, polyethylene glycol, maleic anhydride grafted polypropylene, rare earth β crystal nucleating agent, polycarbodiimide 0.15-0.3 parts and composite antioxidant 0.3 parts. When preparing, talcum powder is premixed with polyethylene glycol, and then the rest of the components are added into the melt through side feeding. The present application uses polyethylene glycol to form hydrogen bonds to shield the heterogeneous nucleation activity of talcum powder, ensuring the growth of β crystal form; it uses in-situ ring-opening half-esterification reaction to build a flexible chemical anchoring layer; and introduces polycarbodiimide to eliminate micro moisture to avoid pore defects. The present application achieves the balance of high ring rigidity and low temperature high toughness of pipe material at low filling amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of chemical engineering and polymer materials technology, specifically to a high ring stiffness polypropylene composition for pipes and its preparation method. Background Technology

[0002] In the industrial application of large-diameter buried drainage pipes, polypropylene is widely used due to its basic physicochemical properties such as corrosion resistance, ease of processing, and relatively low density. Ring stiffness is a core indicator determining the resistance of buried pipes to external pressure loads, and its value is positively correlated with the flexural modulus of the pipe material. To meet engineering standards for the ring stiffness of buried pipes, industrial production typically requires rigidity-enhancing modifications to the polypropylene matrix to ensure that the pipes are not easily deformed or collapsed when subjected to heavy soil and traffic loads underground.

[0003] The current mainstream modification process uses block copolymer polypropylene as the matrix resin and adds a high proportion of inorganic filler, typically 20% to 30% by mass, through co-extrusion. The lamellar structure of talc significantly improves the flexural modulus of the composite material during co-melting extrusion with polypropylene, thereby directly increasing the ring stiffness of the pipe. Simultaneously, to compensate for the brittleness caused by high filler content, β-crystal nucleating agents are often introduced into the formulation to induce the formation of β-crystals with better impact resistance during polypropylene cooling and crystallization. Furthermore, some processes use rigid coupling agents such as aminosilanes to pretreat the inorganic filler to enhance the interfacial bonding between the filler surface and the polypropylene matrix, preventing filler slippage under stress.

[0004] However, the aforementioned conventional preparation systems face an irreconcilable contradiction between rigidity and toughness in practical engineering applications. The fracture edges of talc powder lattice contain numerous magnesium hydroxyl groups and silicon-oxygen bonds. These polar sites possess extremely low nucleation free energy, inducing heterogeneous nucleation of molecular chain segments during polypropylene melt cooling, preferentially generating the high-modulus but highly brittle α-crystalline form. This interfacial nucleation competes with and inhibits the activity of β-crystalline nucleating agents in the system, preventing the formation of sufficient toughening crystalline phases within the matrix. Simultaneously, while conventional silane coupling agents improve interfacial bonding strength, they construct a rigid interfacial layer. When the pipe is subjected to external heavy impact or is in a low-temperature environment, this rigid interface cannot effectively undergo microscopic deformation to buffer and release impact energy. Furthermore, high filler content easily leads to localized powder agglomeration, forming stress concentration points, making existing polypropylene pipes highly susceptible to brittle cracking during low-temperature construction in winter. If the amount of talc is simply reduced or conventional flexible plasticizers are directly introduced in order to improve impact toughness, it will inevitably lead to a sharp drop in the flexural modulus of the material, making the ring stiffness of the pipe unable to meet the technical standards for large-diameter pressure bearing. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a high ring stiffness polypropylene composition for pipes and its preparation method, which solves the problem that when inorganic fillers are used to modify existing high rigidity polypropylene pipes, the fillers easily induce brittle α-crystal growth and lead to deterioration of low-temperature impact resistance. Furthermore, conventional rigid coupling treatment cannot alleviate impact stress, which in turn causes the pipes to be prone to brittle fracture in low-temperature construction environments.

[0006] This invention provides a high ring stiffness polypropylene composition for pipes, using the following technical solution: A high ring stiffness polypropylene composition for pipes, made from raw materials comprising the following parts by weight: 80-85 parts of block copolymer polypropylene; 12-15 parts of finely ground talc; 0.2-0.4 parts of polyethylene glycol; 1.5-2 parts of maleic anhydride-grafted polypropylene; 0.15-0.25 parts of rare earth β-crystal nucleating agent; 0.15-0.3 parts of polycarbodiimide; 0.2-0.5 parts of compound antioxidant.

[0007] By adopting the above technical solution, and by using specific mass fractions of polyethylene glycol, maleic anhydride-grafted polypropylene, and polycarbodiimide, a balance between high ring stiffness and high impact resistance of the pipe is achieved with low filler content.

[0008] Preferably, the block copolymer polypropylene has an ethylene segment mass fraction of 8%-12%, and a melt mass flow rate of 0.5-1.5 g / 10 min at 230°C and a load of 2.16 kg; the median particle size D of the fine talc powder is... 50 The surface is less than or equal to 4 μm and has not undergone chemical coupling treatment.

[0009] Preferably, the number-average molecular weight of the polyethylene glycol is 380-420; and the weight-average molecular weight of the polycarbodiimide is 10,000-15,000.

[0010] Preferably, the maleic anhydride-grafted polypropylene uses homopolymer polypropylene as the matrix, and its maleic anhydride grafting rate is greater than or equal to 1 wt%.

[0011] Preferably, the maleic anhydride-grafted polypropylene is obtained by melt reaction extrusion of raw materials comprising the following parts by weight: 100 parts of homopolymer polypropylene powder, 1.5-2.5 parts of maleic anhydride monomer, 0.1-0.2 parts of free radical initiator dicumyl peroxide, and 0.75-1.25 parts of co-initiator styrene.

[0012] Preferably, the rare earth β-crystal nucleating agent is a binuclear aromatic heterocyclic carboxylic acid lanthanum complex, whose ligands include octanoic acid and phthalic acid; the composite antioxidant is composed of hindered phenolic primary antioxidant 1010 and phosphite secondary antioxidant 168 in a mass ratio of 1:2.

[0013] A method for preparing a high ring stiffness polypropylene composition for pipes includes the following steps: S1. Mix the formulated amount of fine talc powder with polyethylene glycol and pretreat it to obtain talc powder pretreated with polyethylene glycol on the surface. S2. After the block copolymer polypropylene, maleic anhydride grafted polypropylene, rare earth β-crystal nucleating agent, polycarbodiimide and composite antioxidant are dry-mixed evenly, they are fed into the main feed port of a twin-screw extruder with a side feed port for melt blending to obtain a homogeneous melt. S3. The talc pretreated powder obtained in step S1 is forcibly fed into the homogeneous melt obtained in step S2 through the side feed port of the twin-screw extruder to carry out a high-shear in-situ reaction. S4. The blended melt after in-situ reaction is vented, extruded, cooled, drawn into fibers, and pelletized to obtain the final product.

[0014] Preferably, step S1 is implemented as follows: fine talc powder and polyethylene glycol are added into a high-speed mixer, high-speed stirring is started to generate heat through friction to raise the material temperature to 80-90℃, and the temperature is maintained for 8-10 minutes.

[0015] Preferably, in step S2, the temperature of the main feed port and the main melting zone behind the twin-screw extruder is set to 170-190℃; in step S3, the temperature of the side feed port and the high-shear reaction zone behind it is set to 200-210℃, and the screw speed of the twin-screw extruder is controlled at 150-200 rpm.

[0016] Preferably, the length-to-diameter ratio (L / D) of the twin-screw extruder is 44-48; in step S4, the blended melt is vacuum-vented, and the vacuum degree is controlled to be less than or equal to -0.08 MPa.

[0017] This invention provides a high ring stiffness polypropylene composition for pipes and its preparation method. It has the following beneficial effects: 1. This invention pretreats finely ground talc powder with polyethylene glycol (PEG). The terminal hydroxyl groups of PEG form hydrogen bonds with the polar sites on the surface of talc powder, passivating the heterogeneous nucleation activity of talc powder in inducing the formation of α-crystals. This spatial shielding mechanism eliminates the interference of fillers on the crystallization path, allowing rare earth β-crystal nucleating agents in the system to fully exert their effects and stably induce the formation of stress-absorbing β-crystals in the matrix, thereby solving the defect of poor low-temperature impact resistance in traditional high-filler pipes.

[0018] 2. This invention combines a step-feeding process using a twin-screw extruder, enabling the free hydroxyl groups of polyethylene glycol adhering to the surface of talc powder to undergo a ring-opening semi-esterification reaction with maleic anhydride-grafted polypropylene in a high-temperature melt. This process constructs a flexible chemical anchoring layer in situ between the inorganic powder and the polypropylene matrix. Under external load, the flexible chain segments can deform to release impact energy, while the stable chemical bonding prevents microscopic slippage of the filler. This achieves a balance between high ring stiffness and high toughness while reducing the amount of inorganic filler used.

[0019] 3. This invention introduces polycarbodiimide into the formulation. The highly reactive functional groups of polycarbodiimide can irreversibly undergo an addition reaction with water molecules in high-viscosity polypropylene melt, consuming trace amounts of moisture in the system in situ. This mechanism not only utilizes the principle of thermodynamic equilibrium to promote the efficient conduct of the semi-esterification reaction, but also completely eliminates micropore defects formed by water vapor at the phase interface, avoiding crack propagation caused by stress concentration under stress, and ensuring the compactness of the internal structure of the pipe after molding. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the preparation process of the present invention; Figure 2 This is a schematic diagram showing the data comparison of Test Example 1 of the present invention; Figure 3 This is a schematic diagram showing the data comparison of Test Example 2 of the present invention. Detailed Implementation

[0021] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0023] Block copolymer polypropylene (CAS No.: 9010-79-1) has an ethylene segment mass fraction of 8% to 12% and a melt mass flow rate of 0.5 to 1.5 g per 10 minutes at 230°C and a 2.16 kg load.

[0024] The fine talc powder (CAS No.: 14807-96-6) has a median particle size of less than or equal to 4 micrometers and its surface has not undergone any chemical coupling treatment.

[0025] Polyethylene glycol (CAS No.: 25322-68-3) has a number-average molecular weight of 380 to 420.

[0026] Maleic anhydride-grafted polypropylene (CAS No.: 25722-45-6) uses homopolymer polypropylene as the matrix and the maleic anhydride grafting rate is greater than or equal to 1 wt%.

[0027] Rare earth β-crystal nucleating agents are binuclear aromatic heterocyclic carboxylic acid lanthanum complexes, with core ligands including octanoic acid and phthalic acid.

[0028] Polycarbodiimide (CAS No.: 25215-62-7) has a weight-average molecular weight of 10,000 to 15,000.

[0029] The compound antioxidant is composed of hindered phenolic primary antioxidant 1010 (CAS No.: 6683-19-8) and phosphite secondary antioxidant 168 (CAS No.: 31570-04-4) in a mass ratio of 1:2.

[0030] The homopolymer polypropylene (CAS No.: 9003-07-0, melt index of 2 g per 10 minutes), maleic anhydride (CAS No.: 108-31-6), initiator dicumyl peroxide (CAS No.: 80-43-3), and co-initiator styrene (CAS No.: 100-42-5) used to prepare the above-mentioned maleic anhydride-grafted polypropylene are all commercially available conventional basic chemical raw materials.

[0031] Preparation Example 1: This preparation example provides a method for preparing maleic anhydride-grafted polypropylene with a grafting rate of 1 wt%, comprising the following steps: 100 parts by weight of homopolymer polypropylene powder, 1.5 parts by weight of maleic anhydride monomer, 0.1 parts by weight of dicumyl peroxide, and 0.75 parts by weight of styrene were added to a high-speed mixer and mixed at room temperature for 4 minutes to obtain a premix. The premix was fed into a co-rotating twin-screw extruder with an aspect ratio (L / D) of 40 for melt grafting reaction. The temperatures of each section of the extruder were set as follows: 165°C in the feeding zone, 195°C in the reaction zone, and 200°C in the venting zone and die head. The screw speed was controlled at 180 rpm. A high vacuum of -0.09 MPa was applied in the venting zone to remove unreacted monomers and small molecule byproducts. The reaction melt was extruded through the extruder die head, water-cooled, drawn into granules, and dried to obtain maleic anhydride-grafted polypropylene with a maleic anhydride grafting rate of 1 wt%.

[0032] Preparation Example 2: This preparation example provides a method for preparing maleic anhydride-grafted polypropylene with a grafting rate of 1.5 wt%, comprising the following steps: 100 parts by weight of homopolymer polypropylene powder, 2 parts by weight of maleic anhydride monomer, 0.15 parts by weight of dicumyl peroxide, and 1 part by weight of styrene were added to a high-speed mixer and mixed at room temperature for 4 minutes to obtain a premix. The premix was fed into a co-rotating twin-screw extruder with an aspect ratio (L / D) of 40 for melt grafting reaction. The temperatures of each section of the extruder were set as follows: 165°C in the feeding zone, 195°C in the reaction zone, and 200°C in the venting zone and die head. The screw speed was controlled at 180 rpm. A high vacuum of -0.09 MPa was applied in the venting zone to remove unreacted monomers and small molecule byproducts. The reaction melt was extruded through the extruder die head, water-cooled, drawn into granules, and dried to obtain maleic anhydride-grafted polypropylene with a maleic anhydride grafting rate of 1.5 wt%.

[0033] Preparation Example 3: This preparation example provides a method for preparing maleic anhydride-grafted polypropylene with a grafting rate of 2 wt%, comprising the following steps: 100 parts by weight of homopolymer polypropylene powder, 2.5 parts by weight of maleic anhydride monomer, 0.2 parts by weight of dicumyl peroxide, and 1.25 parts by weight of styrene were added to a high-speed mixer and mixed at room temperature for 4 minutes to obtain a premix. The premix was fed into a co-rotating twin-screw extruder with an L / D ratio of 40 for melt grafting reaction. The temperatures of each section of the extruder were set as follows: 165°C in the feeding zone, 195°C in the reaction zone, and 200°C in the venting zone and die head. The screw speed was controlled at 180 rpm. A high vacuum of -0.09 MPa was applied in the venting zone to remove unreacted monomers and small molecule byproducts. The reaction melt was extruded through the extruder die head, water-cooled, drawn into granules, and dried to obtain maleic anhydride-grafted polypropylene with a maleic anhydride grafting rate of 2 wt%.

[0034] Example 1: This example provides a high ring stiffness polypropylene composition for pipes and its preparation method. See attached document. Figure 1 This includes the following steps: By weight, 13.5 parts by weight of fine talc powder and 0.2 parts by weight of polyethylene glycol were weighed and added to a high-speed mixer. High-speed stirring was started, and the material temperature was raised to 85°C by frictional heating. This temperature was maintained for 9 minutes, and the resulting talc powder pretreated with polyethylene glycol was discharged. 82 parts by weight of block copolymer polypropylene, 1.9 parts by weight of maleic anhydride-grafted polypropylene (using the product from Preparation Example 3), 0.2 parts by weight of rare earth β-crystal nucleating agent, 0.2 parts by weight of polycarbodiimide, and 0.3 parts by weight of composite antioxidant were dry-mixed evenly in a low-speed mixer. The mixture was then uniformly fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio (L / D) of 44 and a side feed port. The main melt zone temperature of zones 1 to 4 of the extruder was set to 180°C. After the material fed into the main feeder is completely melted and forms a homogeneous body inside the extruder, the talc pretreated powder is forcibly fed into the melt via a side feeder in zone 5 of the extruder. The temperature of the high-shear reaction zone in zones 5 to 8 of the extruder is set at 205°C. The reacted blend melt enters the vacuum exhaust section at the end of the extruder, with the vacuum level controlled at -0.08 MPa. The melt is then extruded through the extruder die head set at 210°C, cooled and solidified in a water bath, and then drawn and pelletized by a traction machine to obtain a polypropylene composition.

[0035] Example 2: This example provides a high ring stiffness polypropylene composition for pipes and its preparation method, including the following steps: By weight, 12 parts by weight of fine talc powder and 0.2 parts by weight of polyethylene glycol were weighed and added to a high-speed mixer. High-speed stirring was started, and the material temperature was raised to 80°C by frictional heating. This temperature was maintained for 8 minutes, and the resulting talc powder pretreated with polyethylene glycol was discharged. 85 parts by weight of block copolymer polypropylene, 2 parts by weight of maleic anhydride-grafted polypropylene (using the product from Preparation Example 1), 0.15 parts by weight of rare earth β-crystal nucleating agent, 0.15 parts by weight of polycarbodiimide, and 0.2 parts by weight of composite antioxidant were dry-mixed evenly in a low-speed mixer. The mixture was then uniformly fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio (L / D) of 44 and a side feed port. The main melt zone temperature of zones 1 to 4 of the extruder was set to 170°C. After the material fed into the main feeder is completely melted and forms a homogeneous phase inside the extruder, the talc pretreated powder is forcibly fed into the melt via a side feeder in zone 5 of the extruder. The temperature of the high-shear reaction zone in zones 5 to 8 of the extruder is set at 200°C. The reacted blend melt enters the vacuum exhaust section at the end of the extruder, with the vacuum level controlled at -0.08 MPa. The melt is then extruded through the extruder die head, which is set at 210°C, cooled and solidified in a water bath, and then drawn and pelletized by a traction machine to obtain a polypropylene composition.

[0036] Example 3: This example provides a high ring stiffness polypropylene composition for pipes and its preparation method, including the following steps: Weigh 15 parts by weight of fine talc powder and 0.3 parts by weight of polyethylene glycol into a high-speed mixer, start high-speed stirring, and raise the material temperature to 90°C by frictional heating. Maintain the temperature for 10 minutes, and discharge the talc powder pretreated with polyethylene glycol on the surface. Mix 80 parts by weight of block copolymer polypropylene, 2 parts by weight of maleic anhydride grafted polypropylene (using the product from Preparation Example 3), 0.25 parts by weight of rare earth β-crystal nucleating agent, 0.3 parts by weight of polycarbodiimide, and 0.5 parts by weight of composite antioxidant evenly in a low-speed mixer, and then uniformly feed the mixture into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio (L / D) of 44 and a side feed port. The main melt zone temperature of zones 1 to 4 of the extruder is set to 190°C. After the material fed into the main feeder is completely melted and forms a homogeneous body inside the extruder, the talc pretreated powder is forcibly fed into the melt via a side feeder in zone 5 of the extruder. The temperature of the high-shear reaction zone in zones 5 to 8 of the extruder is set at 210°C. The reacted blend melt enters the vacuum exhaust section at the end of the extruder, with the vacuum level controlled at -0.09 MPa. The melt is then extruded through the extruder die head, which is set at 210°C, cooled and solidified in a water bath, and then drawn into fibers and granulated by a traction machine to obtain a polypropylene composition.

[0037] Example 4: This example provides a high ring stiffness polypropylene composition for pipes and its preparation method, including the following steps: By weight, 14.5 parts by weight of fine talc powder and 0.25 parts by weight of polyethylene glycol were weighed and added to a high-speed mixer. High-speed stirring was started, and the material temperature was raised to 85°C by frictional heating. This temperature was maintained for 9 minutes, and the resulting talc powder pretreated with polyethylene glycol was discharged. 81 parts by weight of block copolymer polypropylene, 1.9 parts by weight of maleic anhydride-grafted polypropylene (using the product from Preparation Example 2), 0.18 parts by weight of rare earth β-crystal nucleating agent, 0.25 parts by weight of polycarbodiimide, and 0.3 parts by weight of composite antioxidant were dry-mixed evenly in a low-speed mixer. The mixture was then uniformly fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio (L / D) of 44 and a side feed port. The main melt zone temperature of zones 1 to 4 of the extruder was set to 185°C. After the material fed into the main feeder is completely melted and forms a homogeneous body inside the extruder, the talc pretreated powder is forcibly fed into the melt via a side feeder in zone 5 of the extruder. The temperature of the high-shear reaction zone in zones 5 to 8 of the extruder is set at 205°C. The reacted blend melt enters the vacuum exhaust section at the end of the extruder, with the vacuum level controlled at -0.08 MPa. The melt is then extruded through the extruder die head set at 210°C, cooled and solidified in a water bath, and then drawn and pelletized by a traction machine to obtain a polypropylene composition.

[0038] Example 5: This example provides a high ring stiffness polypropylene composition for pipes and its preparation method, including the following steps: By weight, 12.5 parts by weight of fine talc powder and 0.25 parts by weight of polyethylene glycol were weighed and added to a high-speed mixer. High-speed stirring was started, and the material temperature was raised to 85°C by frictional heating. This temperature was maintained for 9 minutes, and the resulting talc powder pretreated with polyethylene glycol was discharged. 84 parts by weight of block copolymer polypropylene, 1.8 parts by weight of maleic anhydride-grafted polypropylene (using the product from Preparation Example 3), 0.22 parts by weight of rare earth β-crystal nucleating agent, 0.18 parts by weight of polycarbodiimide, and 0.3 parts by weight of composite antioxidant were dry-mixed evenly in a low-speed mixer. The mixture was then uniformly fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio (L / D) of 44 and a side feed port. The main melt zone temperature of zones 1 to 4 of the extruder was set to 175°C. After the material fed into the main feeder is completely melted and forms a homogeneous phase inside the extruder, the talc pretreated powder is forcibly fed into the melt via a side feeder in zone 5 of the extruder. The temperature of the high-shear reaction zone in zones 5 to 8 of the extruder is set at 200°C. The reacted blend melt enters the vacuum exhaust section at the end of the extruder, with the vacuum level controlled at -0.08 MPa. The melt is then extruded through the extruder die head, which is set at 210°C, cooled and solidified in a water bath, and then drawn and pelletized by a traction machine to obtain a polypropylene composition.

[0039] Comparative Example 1: Compared with Example 1, the difference lies in the use of a traditional high-filling formulation and a one-time feeding process.

[0040] Comparative Example 2: Compared with Example 1, the difference is that polycarbodiimide is not added to the formulation, and the block copolymer polypropylene is increased by 0.2 parts by mass to make up for the total amount, while the rest are the same.

[0041] Comparative Example 3: Compared with Example 1, the difference is that polyethylene glycol is not added to the formulation, the block copolymer polypropylene is increased by 0.2 parts by mass to make up for the total amount, and the premixing step only involves dry heat treatment of talc powder, while the rest are the same.

[0042] Comparative Example 4: Compared with Example 1, the difference is that maleic anhydride-grafted polypropylene is not added to the formulation, and the block copolymer polypropylene is increased by 1.9 parts by mass to make up for the total amount, while the rest are the same.

[0043] Comparative Example 5: Compared to Example 1, the difference lies in the change of the feeding process sequence, and the physical isolation and sequential reaction were not constructed.

[0044] Comparative Example 6: Compared to Example 1, the difference lies in replacing the flexible chemical anchoring system unique to this invention with a conventional rigid coupling agent. Specifically, polyethylene glycol, maleic anhydride-grafted polypropylene, and polycarbodiimide are not added to the formulation; an equal amount (2.3 parts by mass) of commercially available titanate coupling agent is used to perform conventional dry surface coupling treatment on the micro-fine talc powder; the treated powder is then mixed evenly with block copolymer polypropylene, rare earth β-crystal nucleating agent, and composite antioxidant, and then added uniformly from the main feed port, without using a side-feeding process; all other extrusion temperature parameters are the same.

[0045] Test Example 1 This test example uses differential scanning calorimetry (DSC) to test the non-isothermal crystallization and melting behavior of the polypropylene compositions prepared in the examples and comparative examples. The feasibility of the crystal form regulation and spatial isolation mechanism in the system is verified through thermodynamic data. See Appendix. Figure 2 .

[0046] The testing was conducted in accordance with GB / T19466.3 standard, and the specific steps are as follows: 1. Cut the test sample from the center area of ​​the standard injection-molded specimen after condition adjustment, weigh the sample using a high-precision analytical balance, and control the mass between 6.5 and 8.5 mg. Place the sample flat in a standard aluminum crucible and press it into a sheet and seal it.

[0047] 2. Place the aluminum crucible containing the sample into the heating cell of the differential scanning calorimeter, using an empty aluminum crucible as a reference, and purge with high-purity nitrogen as a protective gas throughout the process. The nitrogen purging flow rate is set to 50 mL / min.

[0048] 3. Set the instrument temperature program. First, heat the sample from room temperature to 220℃ at a heating rate of 10℃ / min, and then keep it at 220℃ for 5 minutes to completely eliminate the processing thermal history and internal stress of the sample.

[0049] 4. Subsequently, the sample was cooled from 220℃ to 50℃ at a cooling rate of 10℃ / min. During this cooling process, the exothermic crystallization curve of the sample was recorded, and the corresponding crystallization peak temperature Tc was extracted.

[0050] 5. After maintaining the constant temperature for 2 minutes, the sample was heated again from 50℃ to 220℃ at a heating rate of 10℃ / min, and the melting endothermic curve of the second heating was recorded. The melting enthalpy Hmβ of the β crystal form was extracted in the range of 148 to 154℃, and the melting enthalpy Hmα of the α crystal form was extracted in the range of 162 to 168℃.

[0051] 6. Calculate the relative conversion rate of the β crystal form in the composition according to the formula Kβ=Hmβ / (Hmβ+Hmα)×100%.

[0052] Table 1. Thermodynamic test data of crystallization and melting of the composition.

[0053] According to the crystallization and melting data in Table 1, the Tc of the conventional talc-filled system in Comparative Example 1 was 132.4℃, and the Kβ value was 0%. This indicates that the polar sites on the surface of untreated talc possess heterogeneous nucleation capabilities, allowing polypropylene segments to be incorporated into the α-lattice at higher temperatures. In Comparative Example 3, without the addition of polyethylene glycol but containing a rare-earth β-nucleating agent, the Kβ value was 12.8%, indicating that the magnesium hydroxyl groups on the talc surface competitively repel the nucleation-inducing process of the β-nucleating agent. The Kβ values ​​of Examples 1 to 5 ranged from 74.6% to 80.6%, with the Tc shifting towards lower temperatures compared to Comparative Example 1. The thermodynamic data confirm that the terminal hydroxyl groups of polyethylene glycol form hydrogen bonds with the talc surface sites, generating a steric hindrance effect that inhibits the α-nucleation activity of talc, allowing the β-nucleating agent to dominate the crystallization pathway within the system.

[0054] The test results of Comparative Example 5 reflect the influence of the processing technology on the reaction path. Under the same raw material ratio and using a one-time mixed extrusion method, Comparative Example 5 had a Kβ value of 34.5% and a Tc of 129.8℃. Because the reaction sequence was not isolated through stepwise feeding, the anhydride groups of the maleic anhydride-grafted polypropylene reacted directly with polyethylene glycol in the pre-extrusion stage, consuming the polyethylene glycol molecules used to passivate the talc powder. This resulted in partial exposure of the polar sites on the talc powder surface and the re-induction of heterogeneous nucleation of the α-crystal form. Comparative Example 2, without the addition of polycarbodiimide, had a Kβ value reduced to 71.3%, indicating that the water vapor generated by the in-situ reaction and the trace amounts of moisture introduced by the raw materials disrupted the local rheological homogeneity in the high-temperature melt, interfering with the separation of the crystalline phase. Comparative Example 4, without the addition of maleic anhydride-grafted polypropylene, showed crystallization data similar to the examples, indicating that crystal form control occurred normally. However, talc and the resin matrix did not form chemical bonds through a semi-esterification ring-opening reaction. The free polyethylene glycol exhibited a physical lubrication state, failing to achieve stress transfer at the phase interface. This structural defect manifested as a loss of rigidity at the macroscopic mechanical level. The above test data indicate that the stepwise feeding process combined with a specific component ratio controlled the reaction sequence and crystallization nucleation mechanism within the system.

[0055] Test Example 2 This test case examines the macroscopic physical and mechanical properties of the polypropylene compositions prepared in the examples and comparative examples. By using flexural modulus and notched impact strength data at room temperature and low temperature, it verifies the actual influence of the interfacial chemical bonding mechanism and crystal form regulation on the stiffness-toughness balance of the compositions. (See appendix for details.) Figure 3 .

[0056] The testing was conducted in accordance with relevant national standards, and the specific steps are as follows: 1. Dry the polypropylene composition granules obtained in each group in a vacuum drying oven at 80℃ for 4 hours, and then use a standard injection molding machine to injection mold them into standard test strips with dimensions of 80mm×10mm×4mm. Set the barrel temperature of the injection molding machine to 200 to 215℃ and the mold temperature to 40℃.

[0057] 2. Place all injection-molded test specimens in a standard constant temperature and humidity laboratory with a temperature of 23±2℃ and a relative humidity of 50±5% for 48 hours to condition them and eliminate internal stress.

[0058] 3. In accordance with GB / T9341 standard, the bending modulus of the conditioned specimens was tested using an electronic universal testing machine. The support span was set to 64 mm and the loading head descent speed was set to 2 mm / min. Five specimens were tested in each group, and the arithmetic mean was taken.

[0059] 4. In accordance with GB / T1043.1 standard, use a special notch milling machine to machine a type A notch at the center of the side of the test specimen. The bottom radius of the notch is 0.25mm and the remaining width at the notch is 8mm.

[0060] 5. Use a pendulum impact testing machine to test the notched impact strength of the simply supported beam at ambient temperature of 23℃. For low temperature testing, place the specimen in an ultra-low temperature test chamber at a constant temperature of -10℃ for 12 hours. After taking out the specimen, complete the impact test within 3 seconds and record the low temperature notched impact strength data of the simply supported beam. Test 5 specimens for each group and take the arithmetic mean.

[0061] Table 2 Test data of physical and mechanical properties of the composition

[0062] According to the data in Table 2, the macroscopic mechanical properties of the polypropylene composition correspond to its microscopic interface structure and crystal composition. Comparative Example 1, using a conventional system filled with 25 parts by mass of talc, has a flexural modulus of 1462.7 MPa, but its notched impact strength at room temperature and low temperature is only 6.8 kJ / m². 2 and 2.1 kJ / m 2 The system exhibits high brittleness, which is attributed to the large number of α-crystals induced by heterogeneous nucleation of talc and the lack of effective interfacial bonding between the inorganic powder and the resin matrix. In Examples 1 to 5, when the amount of talc was reduced to 12 to 15 parts by mass, the flexural modulus remained above 1639.2 MPa, the room-temperature notched impact strength ranged from 38.3 to 42.6 kJ / m², and the low-temperature notched impact strength ranged from 7.9 to 9.3 kJ / m². Despite the reduction in filler content, no loss of rigidity was observed, and the toughness increased, verifying the existence of an effective stress transfer and dissipation mechanism in the system.

[0063] Comparative Example 4, without the addition of maleic anhydride-grafted polypropylene, showed a flexural modulus reduced to 1315.6 MPa. In the absence of the chemically anchored network constructed by the ring-opening semi-esterification reaction, polyethylene glycol only functions as a lubricant. Under flexural loads, talc particles readily undergo interfacial micro-slippage and debonding within the continuous polypropylene phase, failing to bear the stress transferred from the matrix. Comparative Example 6, treating talc with a conventional aminosilane coupling agent, achieved a flexural modulus of 1593.2 MPa, indicating that rigid chemical bonding can achieve stress transfer; however, its low-temperature notched impact strength was only 2.9 kJ / m². 2 The rigid interface formed by the silane coupling layer cannot deform and release energy when subjected to high strain rate external force impact, while the anchoring structure constructed by polyethylene glycol flexible segments in the embodiment has a stress buffering effect at low temperature.

[0064] Comparative Example 2, lacking polycarbodiimide, showed a decrease in notched impact strength to 17.6 kJ / m at both room temperature and low temperature. 2 and 3.5kJ / m 2 Unremoved reaction byproducts (water) and physically introduced moisture trigger micro-foaming in the high-temperature environment of the extruder, forming multiple voids and defects at the interface between talc and the polypropylene matrix. This leads to rapid crack propagation at these defects upon impact. Comparative Example 3, without polyethylene glycol (PEG) passivation of talc, exhibits high modulus and low impact strength, corresponding to the system's matrix primarily consisting of a tough α-crystalline form. Comparative Example 5, using a one-time mixing and feeding process, shows low flexural modulus and notched impact strength. This one-time feeding prevents maleic anhydride-grafted polypropylene from binding to free-terminal hydroxyl groups in the correct reaction sequence, disrupting the PEG shielding of talc nucleation sites. Consequently, the system fails to form a regular crystalline barrier and anchoring mechanism. The mechanical data confirm the engineering necessity of a stepwise lateral feeding process to control reaction competition paths.

[0065] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high ring stiffness polypropylene composition for pipes, characterized in that, Made from the following ingredients in parts by weight: 80-85 parts of block copolymer polypropylene; 12-15 parts of finely ground talc; 0.2-0.4 parts of polyethylene glycol; 1.5-2 parts of maleic anhydride-grafted polypropylene; 0.15-0.25 parts of rare earth β-crystal nucleating agent; 0.15-0.3 parts of polycarbodiimide; 0.2-0.5 parts of compound antioxidant.

2. The high ring stiffness polypropylene composition for pipes according to claim 1, characterized in that: The block copolymer polypropylene has an ethylene segment mass fraction of 8%-12%, and a melt mass flow rate of 0.5-1.5 g / 10 min at 230°C and a load of 2.16 kg; the median particle size D of the fine talc powder is... 50 The surface is less than or equal to 4 μm and has not undergone chemical coupling treatment.

3. The high ring stiffness polypropylene composition for pipes according to claim 1, characterized in that: The number-average molecular weight of the polyethylene glycol is 380-420; the weight-average molecular weight of the polycarbodiimide is 10000-15000.

4. The high ring stiffness polypropylene composition for pipes according to claim 1, characterized in that: The maleic anhydride-grafted polypropylene uses homopolymer polypropylene as the matrix, and its maleic anhydride grafting rate is greater than or equal to 1 wt%.

5. The high ring stiffness polypropylene composition for pipes according to claim 4, characterized in that: The maleic anhydride-grafted polypropylene is obtained by melt reaction extrusion of raw materials comprising the following parts by weight: 100 parts of homopolymer polypropylene powder, 1.5-2.5 parts of maleic anhydride monomer, 0.1-0.2 parts of free radical initiator dicumyl peroxide, and 0.75-1.25 parts of co-initiator styrene.

6. The high ring stiffness polypropylene composition for pipes according to claim 1, characterized in that: The rare earth β-crystal nucleating agent is a lanthanum organic complex type β-crystal nucleating agent; The composite antioxidant is composed of hindered phenolic primary antioxidant 1010 and phosphite secondary antioxidant 168 in a mass ratio of 1:

2.

7. A method for preparing a high ring stiffness polypropylene composition for pipes according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Mix the formulated amount of fine talc powder with polyethylene glycol and pretreat it to obtain talc powder pretreated with polyethylene glycol on the surface. S2. After the block copolymer polypropylene, maleic anhydride grafted polypropylene, rare earth β-crystal nucleating agent, polycarbodiimide and composite antioxidant are dry-mixed evenly, they are fed into the main feed port of a twin-screw extruder with a side feed port for melt blending to obtain a homogeneous melt. S3. The talc pretreated powder obtained in step S1 is fed into the homogeneous melt obtained in step S2 through the side feed port of the twin-screw extruder to carry out a high-shear in-situ reaction. S4. The blended melt after in-situ reaction is vented, extruded, cooled, drawn into fibers, and pelletized to obtain the final product.

8. The method for preparing a high ring stiffness polypropylene composition for pipes according to claim 7, characterized in that: The specific implementation method of step S1 is as follows: put fine talc powder and polyethylene glycol into a high-speed mixer, start high-speed stirring to generate heat through friction to raise the material temperature to 80-90℃, and keep it at a constant temperature for 8-10 minutes.

9. The method for preparing a high ring stiffness polypropylene composition for pipes according to claim 7, characterized in that: In step S2, the temperature of the main feed port and the main melting zone behind the twin-screw extruder is set to 170-190℃; in step S3, the temperature of the side feed port and the high-shear reaction zone behind it is set to 200-210℃, and the screw speed of the twin-screw extruder is controlled at 150-200 rpm.

10. The method for preparing a high ring stiffness polypropylene composition for pipes according to claim 7, characterized in that: The length-to-diameter ratio (L / D) of the twin-screw extruder is 44-48; in step S4, the blended melt is vacuum-vented, and the vacuum degree is controlled to be less than or equal to -0.08 MPa.